Both T cell receptor (TcR)-CD3 complex and CD2 increase the tyrosine kinase activity of p56lck. CD2 can mediate TcR-CD3-independent and CD45-dependent activation of p56lck. - Danielian, S; Alcover, A; Polissard, L; Stefanescu, M; Acuto, O; Fischer, S; Fagard, R (1992)
T cell activation by triggering the T cell receptor (TcR)-CD3 complex leads to a dramatic increase in tyrosine phosphorylation of multiple cellular proteins. To date, there has been no direct evidence on the identity of the tyrosine kinase activity implicated in this signaling pathway. In this study, we demonstrate that activation of human T cells with anti-CD3 monoclonal antibody increases tyrosine kinase activity of p56lck. This extends our previous findings which demonstrated the involvement of p56lck kinase activity in the CD2 signal transduction pathway. The results from peripheral blood lymphocytes and Jurkat cell line showed in both cases an early and transient change in the specific activity of p56lck, followed by a shift to a higher apparent molecular mass. Therefore, to test directly the role of TcR-CD3 in CD2-induced activation of p56lck, we utilized mutant variants of the Jurkat cell line lacking in cell surface TcR-CD3. We found that cell surface expression of TcR-CD3 is not required for the activation of p56lck via CD2 but is necessary for the appearance of the reduced-electrophoretic-mobility form of p56lck observed after CD2 triggering. By isolating CD45- mutants from Jurkat cells, we observed that surface expression of the tyrosine phosphatase CD45 is required in order to increase p56lck activity following CD2 stimulation, while CD4-induced activation of the kinase remained unchanged. These data provide evidence for a specific functional linkage between CD2 and p56lck, in which CD45 may play an essential role.